Positive Impact of Using Learning Management Systems in the Higher Education Level - Lokollo, Lambertus J.; Kempa, Rudolf; Manoppo, Yance; Latuny, Leny S.; Lumbantoruan, Jitu Halomoan (Universitas Pendidikan Ganesha, 2023)
Almost all universities in urban areas already use Learning Management Systems (LMS). This obligation forces lecturers to prepare material and put it into Learning Management Systems (LMS). But facts. There are 63% of lecturers who have difficulty compiling online material. The hope is that using Learning Management Systems (LMS) can improve student learning outcomes. This research aims to determine the positive impact of implementing learning in higher education assisted by Learning Management Systems (LMS). The research wants to find out the obstacles and difficulties in implementing Learning Management Systems (LMS) learning. The research method used is a survey by distributing instruments. Data collection technique, by distributing instruments to 132 people consisting of lecturers and students who were directly involved in the learning process. The analysis technique averages the instruments that have been assessed by students and lecturers. The average results are then interpreted into sentences. As a result, lecturers find obstacles and difficulties in using the learning management system in the learning process. Obstacles and difficulties lie in the implementation of material, the use of learning models, and difficulties in assessing student attitudes and skills. It was found that the material was not included in the Learning Management Systems (LMS) but still distributed different media materials so that learning was less effective. Assessment indicators are also not given to students, so students cannot measure their abilities. In conclusion, every lecturer must prepare materials, models, and assessment instruments before using Learning Management Systems (LMS) as a tool to help implement learning in higher education.